Teknik Pembibitan Tanaman Ketapang (Terminalia catappa L.) di UPTD BSPTH Dinas Kehutanan Provinsi Sumatera Barat - Sundari Permata Sari; Abdul Razak (GLOBAL SCIENTS PUBLISHER, 2026)
Terminalia catappa L. (ketapang) is a multipurpose tree species that is widely found in tropical coastal areas and has significant ecological and economic value. This study aimed to describe the nursery technique of Terminalia catappa L. at the UPTD Certification and Forest Plant Propagation Center (BSPTH), West Sumatera Forestry Service. The method used was direct observation and active participation in all nursery activities, supported by literature review. The results showed that the nursery of T. catappa was carried out generatively using natural seedlings collected from Pantai Tiram, Padang Pariaman Regency. The process consisted of three main stages: (1) collection of seedlings with a height of 15–30 cm with healthy stems and leaves; (2) weaning of seedlings into polybags (12 × 17 cm) with growing medium of soil, compost, and rice husk; and (3) routine maintenance including watering, fertilizing, weeding, and pest control until seedlings were ready for distribution. The success of T. catappa propagation was strongly determined by seedling quality, careful extraction to maintain root integrity, growing medium composition, shade intensity management, and consistency of maintenance activities. This study provides valuable information for forest rehabilitation programs, particularly in coastal replanting efforts in West Sumatera.